Interspecies and spatial differences in the shell microbiome of Atlantic rock crab Cancer irrotatus and European green crab Carcinus maenas from Atlantic Canada - Koepper, Svenja; Kelley, Shannon; Thakur, Krishna Kumar; Clark, K. Fraser (Frontiers in Marine Science, 2023)
Introduction The native Atlantic rock crab (Cancer irrotatus) and the invasive European green crab (Carcinus maenas) are commercially and ecologically important crustacean species in Atlantic Canada. The importance of microbiomes for host health and ecology has been recognized in many species, although very few studies have focused on crustaceans or their external shell microbiome. This is the first-ever study to characterize and analyze the microbial communities associated with the external carapace of C. irrotatus and C. maenas. Methods Microbiome samples were collected from three locations in Atlantic Canada, processed using standard 16S Illumina MiSeq PE250 sequencing and analyzed with the open-access QIIME2 software. Results Taxonomic classification of the microbial compositions, as well as alpha- and beta diversities, reveal that the shell microbiome differs by host species between C. irrotatus and C. maenas sampled from the same location and between C. irrotatus sampled from different locations. Interestingly, the differences are greater between species at the same location than between locations for the same species. Discussion These are the first-ever results showing that the crustacean shell microbiome not only depends on geographical factors but also on intrinsic factors specific to the host species. This implies that crustaceans exert some impact on their shell microbiome, potentially selecting beneficial taxa. These are important findings that could elucidate contributing factors of crustacean shell diseases that are still poorly understood.